2021
DOI: 10.1101/2021.11.16.468757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of Taxon-Sampling Schemes on Bayesian Molecular Dating under the Unresolved Fossilized Birth-Death Process

Abstract: Evolutionary timescales can be estimated using a combination of genetic data and fossil evidence based on the molecular clock. Bayesian phylogenetic methods such as tip dating and total-evidence dating provide a powerful framework for inferring evolutionary timescales, but the most widely used priors for tree topologies and node times often assume that present-day taxa have been sampled randomly or exhaustively. In practice, taxon sampling is often carried out so as to include representatives of major lineages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…Subsampling a fossil record using the unresolved FBD can be accurate with an evenly sampled clade such as cetaceans (Barido-Sottani et al 2019), but can be highly inaccurate if the fossils have limited phylogenetic information (O’Reilly and Donoghue 2020). A recent analysis of mammals (Luo et al 2021), however, found that fossil sampling density does not have linear effects on divergence time estimates. Altogether, it is difficult to generalize about the best models, unless prior knowledge is contradicted.…”
Section: Discussionmentioning
confidence: 96%
“…Subsampling a fossil record using the unresolved FBD can be accurate with an evenly sampled clade such as cetaceans (Barido-Sottani et al 2019), but can be highly inaccurate if the fossils have limited phylogenetic information (O’Reilly and Donoghue 2020). A recent analysis of mammals (Luo et al 2021), however, found that fossil sampling density does not have linear effects on divergence time estimates. Altogether, it is difficult to generalize about the best models, unless prior knowledge is contradicted.…”
Section: Discussionmentioning
confidence: 96%
“…Subsampling a fossil record using the unresolved FBD can be accurate with an evenly sampled clade such as cetaceans ( Barido-Sottani et al 2019 ), but can be highly inaccurate if the fossils have limited phylogenetic information ( O’Reilly and Donoghue 2020 ). An analysis of mammals ( Luo et al 2021 ), however, found that fossil sampling density does not have linear effects on divergence time estimates. Altogether, it is difficult to generalize about the best models, unless prior knowledge about node ages is contradicted.…”
Section: Discussionmentioning
confidence: 98%
“…5). Accordingly, we prefer not to give this group familial rank basal to Mastotermitidae, while noting that the reliance of the recent analysis on the fossilized birth-death (FBD) model can be problematic in the placement of fossil taxa and some estimations, particularly as not all fossils are appropriate for the FBD process (e.g., Luo et al, 2020Luo et al, , 2022.…”
Section: Clarifying the Taxonomy Of The Earliest-diverging Lineages A...mentioning
confidence: 99%